Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Karyawan PT Romindo Primavetcom di Jakarta - Al Habib Muzakki; Purwatiningsih Purwatiningsih; Ratih Setyo Rini (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2025)
This study aims to analyze the effect of work motivation and work discipline on employee performance at PT Romindo Primavetcom. The research utilized a quantitative approach, with data collected through questionnaires distributed to 55 respondents. The data was analyzed using multiple linear regression to examine the relationship between the variables. The results show that work motivation has a significant partial effect on employee performance, as indicated by the t-value (3.772) being greater than the t-table (2.00575) and a significance value (0.000) below 5%. Similarly, work discipline significantly affects employee performance with a t-value (2.911) greater than the t-table (2.00575). Simultaneously, work motivation and discipline collectively have a significant effect on employee performance, demonstrated by the F-value (83.411) exceeding the F-table (3.18) and a significance value (0.000) below 5%. The conclusion of this study is that both work motivation and discipline, whether partially or simultaneously, significantly influence employee performance. PT Romindo Primavetcom can enhance employee performance by focusing on effective motivation programs, such as providing incentives, and enforcing consistent discipline policies. This approach can foster a more productive work environment and support the achievement of organizational goals.